Participation in Child Protection Theorizing Children's Perspectives - Duncan, Mandy (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
There have long been doubts within social work about the viability of reconciling participatory practice with the statutory power that comes hand-in-hand with child protection work. This book explores this issue by proposing an original theory of children's participation within statutory child protection interventions. It prioritises children's voices through presentation of a wide collection of children's experiences of the child protection system including three unique in-depth accounts. Identifying the different ways in which children engage with professionals in the child protection process, Duncan explores why they act in the ways that they do. The book reveals why some children are sceptical participants or become disaffected with the system whilst others participate more positively within it. Participation in Child Protection will be of interest to students and scholars across a range of disciplines, including social work, sociology, psychology, counselling, law and education, as well as child protection professionals such as social workers, child protection police officers, health visitors and teachers. .